Ethmoid Sinus Mucocele Penetrating the Anterior Skull Base: A Case Report - Byung Jae Kang; Min Suk Kim; Kukjin Nam; Min Young Seo (Journal of Rhinology)
Sinus mucoceles are nonmalignant cystic tumors lined by non-neoplastic epithelium, typically involving the frontal and ethmoid sinuses. Although it is common for these mucoceles to cause destruction of surrounding bone tissue due to their growth, cerebrospinal fluid leaks resulting from skull base penetration by an ethmoid sinus mucocele have rarely been reported. A 24-year-old male patient presented with right proptosis and right periorbital pain, who underwent bilateral endoscopic sinus surgery 12 years ago. Endoscopic sinus surgery was performed to treat the right ethmoid sinus mucocele, and confirmed the presence of a basal skull defect during surgery. We reconstructed the skull base defect using septal cartialge and free mucosal graft. The symptoms were completely resolved after surgery and no cerebrospinal fluid leakage was noted during follow up period. This case report highlights a rare instance of direct mucocele extension to the skull base.